Human Resource Development Strategy in KSU Pelita Agribusiness Cianjur Regency - Priadi, Getama; Ramly, Amir Tengku; Andriyansah, Andriyansah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Human Resource Development (HRD) is very important to improve and maintain employees so that they become reliable resources for the organization. This thesis discusses human resource development at KSU Pelita Agribusiness, which must be carried out continuously and adapted to changes in the company's internal and external environment. The aim is to prepare human resources to be ready to face business developments and uncertainties quickly and flexibly so that an appropriate and targeted HR development strategy is needed. This research involved 4 people from KSU Pelita Agribusiness as well as 3 practitioners, academics, and the Cianjur Regency Cooperative Service. Initial data was obtained through SWOT analysis which resulted in four alternative strategies: recruitment of professional human resources and appropriate employee training, implementation of company SOPs and special training according to SOPs, clear and consistent implementation of SOPs, and HR rotation through re-interviews or fit and proper tests. AHP analysis shows that strategic priorities that can be implemented by KSU Pelita Agribusiness are providing training, motivation, and performance improvement (value: 0.570), rotating HR (value: 0.180), implementing company SOPs (value: 0.177), recruiting HR (value: 0.073).